Exploring the cross-talk between liver and vessels through increased morning blood pressure in hypertension. (14th October 2021) - Kakouri, N; Konstantinidis, D; Siafi, E; Tatakis, F; Drogkaris, S; Polyzos, D; Thomopoulos, C; Koullias, M; Tsioufis, K
Abstract: Background: Nonalcoholic fatty liver disease (NAFLD) is associated with hypertension and predicts future cardiovascular events. Purpose: To compare blood pressure (BP) morning surge assessed by ambulatory blood pressure monitoring (ABPM) in hypertensive patients with and without NAFLD. Methods: Sixty-five consecutive patients with newly diagnosed essential hypertension (age 57±10 years, office BP 139/87±16/9 mmHg) were studied. In all patients a routine biochemical blood examination was undertaken while BP morning surge was automatically calculated by a Spacelabs 90207 device. NAFLD was confirmed by a liver ultrasound. Accordingly, patients were divided in those with and without NAFLD (control group). Results: Patients with NAFLD (n=44) in comparison with controls (n=21) had similar 24h systolic (141.6±9.9 vs 143.2±10.4 mmHg) and diastolic BP (83.6±10.23 vs 84.7±9.53 mmHg) while office BP was also not different between groups (p=NS). However, those with NAFLD were younger (55±10 vs 61±9 years, respectively, p=0.046), had higher body mass index (32.5±4.5 vs 26.3±3.8 kg/m 2, p<0.001), glomerular filtration rate (93.8±17 vs 82.6±9.2 ml/min/1.73m 2, p=0.013), and higher levels of morning BP surge (14.29±8.5 vs 5.92±9.01mmHg, p=0.034), compared to the non-NAFLD group. Standard deviation of BP, average real variability, coefficient of variation and dipping status were not different between groups. Conclusions: At the same levels of clinic and ambulatory BP, hypertensive patients with NAFLD compared to their non-NAFLD counterparts demonstrated increased morning surge BP levels. Our finding suggests that NAFLD may demonstrate a detrimental effect to early-morning at variance to the whole-day hemodynamics. Funding Acknowledgement: Type of funding sources: None.